The effect of ethanolic plant extract from cosmos caudatus against salmonella typhi and streptococcus agalactiae - Muhammad Alif Syazwan Mohd Basree (2022)
Cosmos caudatus or Ulam Raja have been used as a traditional medicine to treat various diseases. The emergence of disease resistance toward antibiotics has become a considerable problem and caused the need to develop new antimicrobials from other alternative sources. This study is conducted to investigate the antimicrobial activity of plant extract from C. caudatus against Salmonella typhi and Streptococcus agalactiae. The Agar diffusion method with ethanolic C. caudatus extract was used to test the antimicrobial activity of the plant toward Salmonella typhi and Streptococcus agalactiae. This study’s results show no inhibition zone produced on the Mueller Hinton Agar (MHA) for both tested bacteria. In conclusion, there are no antimicrobial activities of ethanolic C. caudatus extract against S. typhi and S. agalactiae. Keywords: Cosmos caudatus, antimicrobial, Salmonella typhi, Streptococcus agalactiae